Concise Syntheses of α-Galactosyl Ceramide, d-ribo-Phytosphingosine, and Ceramide - Yen, Yu-Fen; Sawant, R. C.; Luo, Shun-Yuan (Synthesis, 2013)
Total syntheses of α-galactosyl ceramide, d-ribo-phytosphingosine, and ceramide through an α-galactosyl phytosphingosine derivative as a common synthon were accomplished in overall yields of 26%, 15%, and 20% in nine, seven, and eight steps, respectively, starting from an acetonide-protected d-lyxose derivative. This short and efficient protocol involved protection and glycosylation of the acetonide-protected d-lyxose with d-galactosyl iodide as a key step. The resulting α-linked disaccharide was subsequently transformed into α-galactosyl ceramide, phytosphingosine, and ceramide.
Keywords: glycosylations; glycolipids; total synthesis